Gamic seed production of Tithonia diversifolia Hemsl.) A. Gray. sowing and establishment - Padilla, C.; Rodríguez, Idalmis (Cuban Journal of Agricultural Science, 2021)
This review aims to spread the advances in the production of gamic seed of Tithonia diversifolia Hemsl.) A. Gray. and the establishment in this way. The germination of this species is reported, as well as the ways to increase it through dormancy detection, seed conservation, types of substrates and their performance under laboratory and nursery conditions, as well as the variables related to the morphostructure of seedlings until transplantation. It is shown that germination percentages between 50 and 90 % can be reached when the seeds are harvested at the optimum moment and treatments that favor viability and germination are applied. The integral agronomic management allowed defining the best harvest time and the effects on different practices that allow the appearance of uniform flowering flows and obtaining yields of the order of 20-30 kg of pure germinable seed (PGS). Results are discussed and reported on the real possibility of achieving satisfactory establishments and acceptable biomass production when different practices are used to protect gamic seeds with plant and organic wastes. It is showed for the first time, the advantages of the sowings by gamic seed in relation to the plantations by cuttings and in bags for the forage yield (11.68 vs 9.48 and 9.92 t DM.ha-1) and for the populations (10.55 vs 5.88 and 10.88 plants.m-2) respectively, in the establishment cut. The advances made allow the promotion of seed production and achieve a greater introduction and generalization of this species, which in turn can contribute to an increase in food production. Key words: Germination, Tithonia diversifolia, pure germinable seed (PGS), establishment, production and gamic reproduction.